Growth patterns of microfinance clients - Evidence from Sub-Saharan Africa - Adalbert Winkler; Charlotte Wagner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We provide evidence on the growth patterns of microfinance clients. Our analysis is motivated by the debate on the impact of microfinance on client income and growth. Based on loan-level data from close to 40,000 clients in Sub-Saharan Africa we make use of an econometric approach widely employed in the firm growth literature. Results show that on average clients exhibit substantial growth between two consecutive loans. Moreover, there is a non-linear relationship between initial client size and growth: smaller businesses show higher growth rates which is marginally counteracted by positive growth of the very large clients. Results also indicate that growth rates decline in the course of the lending relationship. Overall our results provide econometric support for the largely anecdotal evidence presented by microfinance practitioners that their clients grow. At the same time they suggest that the equilibrium size of most clients remains small.
Keywords: D22; G21; L25; 330